The Effect of Using Picture Word Card Media on the Beginning Reading Ability of Class 1 Students at SDN Inpres 2 Tangga - Haerunnisah, Haerunnisah; Sholihin, Sholihin; Cahyadi, Anggih Tri (JUPE : Jurnal Pendidikan Mandala, 2024)
The aim of this research is to determine the effect of using picture word card media on the initial reading ability of class I students at SDN Inpres 2 Tangga. This type of research is experimental research, the research design used is Pre_Experimental Design with the One-Group Pretest-Posttest Design model. The data collection techniques used in this research are tests, observation and documentation. Data analysis uses descriptive analysis and inferential analysis. The subjects in this research were class I students at SDN Inpres 2 Tangga, totaling 14 students consisting of 10 boys and 4 girls. The research results show that the average pretest score is 45.3571 and the average posttest score is 69.6429. This shows that there is an influence on the initial reading ability of class I students at SDN Inpres 2 Tangga and the results of the Paired Sample hypothesis test show that the significance value of 0.001 is smaller than 0.05, so Ho is rejected and Ha is accepted. "There is an influence of the use of picture word cards on ability beginning reading for class I students at SDN Inpres 2 Tangga."